Legal Education at the University of Olomouc (Sixteenth to Nineteenth Century) - Janišová, Jana; Janiš, Dalibor (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2025)
This study is devoted to the issue of legal education at the University of Olomouc in the period from the 16th to the 19th century. The University was founded in the 16th century by the bishops of Olomouc in cooperation with the Jesuit Order. Originally, it did not have an independent faculty of law and law was taught privately at the expense of the Moravian Estates. In 1725, the Estates Academy was founded in Olomouc to educate young noblemen, especially for the civil service (officers, clerks). Lawyers associated with the University taught law at the academy. In 1784, an independent faculty of law was established within the University (formally lyceum). Studies spanned three years; from 1810 then four years. All basic law subjects were taught at the faculty. Josef Vratislav Monse, a prominent Enlightenment scholar and lawyer, worked at the faculty. However, in the middle of the 19th century, the faculty of law was abolished, as were most other faculties.
Keywords: education; university; legal history; Moravia